FIVE YEARS CHARACTERISTIC OF URETHRAL TRAUMA IN TERTIARY HOSPITAL IN WEST JAVA FROM 2013-2017 - Agung Nugroho, Tri Sunu; Adi, Kuncoro (Indonesian Journal of Urology, 2021)
Objective: In this study, we try to describe the characteristics of patients with urethral trauma in Hasan Sadikin Hospital Bandung from 2013 to 2017. Material & Methods: The data were taken retrospectively from medical records in the Department of Urology with the permission of the ethical committee. The patient characteristics were then classified according to their age, etiology of trauma, location of trauma, grade of trauma, associated trauma, and initial management. Results: The number of trauma cases in Hasan Sadikin Hospital during 2013-2017 was 20.489, 477 of which (2.33%) were urogenital trauma. Of the total urogenital trauma, there were 124 patients with urethral trauma, male patients were more common (84.67%), with an average age of 34.67 (1-82) years. Seventy two patients (58.06%) were iatrogenic trauma (catheter instrumentation 44.35%, circumcision 6.45%, and others 7.25%), and fifty two patients (41.94%) were non-iatrogenic trauma (traffic accident 31.45%, falls from a height 7.25%, and occupational accident 3.22%). In non-iatrogenic trauma group, 40 patients (76.92%) had posterior urethral trauma and 12 patients (23.08%) had anterior urethral trauma. We found 22 (42.31%) of 52 patients with non-iatrogenic trauma were AAST grade I-II and 30 patients (57.69%) were AAST grade III-V. In patients with posterior urethral trauma, 25 patients (62.5%) had pelvic fractures. There were 10 patients (19.23%) who underwent primary endoscopic realignment within the first 72 hours while 30 patients (57.69%) underwent delayed urethroplasty 3 months after trauma, and the rest (23.08%) were treated conservatively. Conclusion: Urethral trauma in males occurs more frequently than in females. with the most common cause were catheter instrumentation (iatrogenic) and traffic accidents (non iatrogenic). Posterior urethral traumas had higher incidence than anterior urethral traumas, which were commonly associated with pelvic fractures.